Bricker ileal conduit diversion with ICG technique in 10 steps - Clara Dujardin; Fabrice Narducci; Delphine Hudry; Arnaud Villers; Gautier Marcq; Carlos Martinez Gomez (Gynecologic Oncology Reports)
The Bricker ileal conduit is a widely used incontinent urinary diversion, commonly performed after pelvic exenteration. Described by Bricker in 1950 (Bricker, 1950), it remains popular due to low complication rates and surgical simplicity (Martínez-Gómez et al., 2021). Early postoperative complications include intestinal or urinary fistulas, while late ones involve ureteral stenosis (Hétet et al., 2005).In women’s cancers, pelvic exenteration often follows radiotherapy or retroperitoneal dissection during aortic lymphadenectomy, involving extensive left-sided ureteral dissection, which complicates ureteral vascularization.ICG (indocyanine green) is a safe, widely used technique in oncologic surgery to assess tissue vascularization, reducing fistula and stenosis risks in ileoureteral and ileoileal anastomoses.The urinary conduit is made from a 20 cm ileal segment, with ureters anastomosed separately to the proximal end. ICG is injected intravenously to assess ureteral and anastomotic vascularization. The distal end forms a cutaneous stoma.